The Effectiveness of Corporate Governance Components as a Control Mechanism in Detecting Tax Avoidance When the Company is Under Financial Pressure - Palupi, Indarti Diah; Kurniawati, Lintang; Wijayanto, Kusuma (Universitas Muhammadiyah Surakarta, 2021)
This study investigates the effectiveness of corporate governance components in detecting corporate tax avoidance and how effectiveness is affected when firms are under financial pressure. This study uses three components of corporate governance: board of directors, board of commissioners, and audit committees while corporate tax avoidance is measured using effective tax rate (ETR). This study employs data from manufacturing companies listed on the Indonesian Stock Exchange. Sample was selected using purposive sampling method. Data analysis was conducted on 163 panel data from 62 companies in 2016 - 2018 using moderated regression analysis. The results prove that proportion of independent directors and audit committees as predictors of ETR. Whereas proportion of independent commissioners and board of directors and board of commissioners meeting ratio have no effect on ETR. It also shows that financial pressure moderates the relationship between the proportion of independent directors and ETR. Financial pressure also moderates the relationship between the audit committee and ETR. On the contrary, financial pressure does not moderate the association of independent commissioners and ETR. The results also show that external audit as a control variable related to ETR. This study contributes to the literature on the importance of the effectiveness of corporate governance components in reducing tax avoidance and how financial pressure affects their effectiveness.